2021
DOI: 10.3389/fnut.2021.617721
|View full text |Cite
|
Sign up to set email alerts
|

Cooking at Home and Adherence to the Mediterranean Diet During the COVID-19 Confinement: The Experience From the Croatian COVIDiet Study

Abstract: Introduction: The primary aims of this study were to evaluate the changes in dietary behavior among the Croatian adult population during the COVID-19 outbreak and to explore the impact of confinement on cooking habits.Methods: The study was based on results from COVIDiet_Int cross-sectional study—a part of COVIDiet project (NCT04449731). A self-administered online questionnaire was used to assess the frequency of food consumption, eating habits, and sociodemographic information. A total number of 4,281 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
65
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 52 publications
11
65
1
2
Order By: Relevance
“…With the patterns of healthy food consumption and spending more time to cook, this paper suggests that life has changed in all countries and even though the population feels depressed and anxious they accept the new normal and use the time they have now to adopt sustainable and healthy lifestyles. Many studies reported more frequent home cooking during pandemic (Skotnicka et al, 2021; Pfeifer et al, 2021 ; Rodríguez-Pérez et al, 2020 ; Sidor and Rzymski, 2020 ; Zhang et al, 2020 ). Moreover, a higher frequency of home cooking was associated with greater adherence to the Mediterranean Diet in Croatia ( Pfeifer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the patterns of healthy food consumption and spending more time to cook, this paper suggests that life has changed in all countries and even though the population feels depressed and anxious they accept the new normal and use the time they have now to adopt sustainable and healthy lifestyles. Many studies reported more frequent home cooking during pandemic (Skotnicka et al, 2021; Pfeifer et al, 2021 ; Rodríguez-Pérez et al, 2020 ; Sidor and Rzymski, 2020 ; Zhang et al, 2020 ). Moreover, a higher frequency of home cooking was associated with greater adherence to the Mediterranean Diet in Croatia ( Pfeifer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported more frequent home cooking during pandemic (Skotnicka et al, 2021; Pfeifer et al, 2021 ; Rodríguez-Pérez et al, 2020 ; Sidor and Rzymski, 2020 ; Zhang et al, 2020 ). Moreover, a higher frequency of home cooking was associated with greater adherence to the Mediterranean Diet in Croatia ( Pfeifer et al, 2021 ). Having provided the evidence of positive sights of this unprecedent crisis, the study also presents important cues that need to be taken into account in what concerns the supply and distribution of food as well as helping to reinforce the endeavor of being more sustainable and healthier.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in nutritional behaviour may be dependent upon the country examined. In Croatia, more than 4000 participants in a study revealed cooking frequency increased during the COVID-19 pandemic lockdown with an increased consumption of vegetables, legumes and seafood [ 59 ].…”
Section: Changes In Dietary Behaviour During the Pandemic And Their Consequencesmentioning
confidence: 99%
“…Social isolation during the pandemic-induced lockdown or quarantine resulted in more severe effects on nutritional status [ 58 ]. In a Belgian study, 10% of participants often or sometimes could not afford to eat a healthy diet during confinement [ 59 ]. Tendencies for fruit and vegetable consumption decreased and the consumption of soft drinks, sweets, bread and salty snacks increased [ 60 , 61 , 62 ].…”
Section: Changes In Dietary Behaviour During the Pandemic And Their Consequencesmentioning
confidence: 99%
See 1 more Smart Citation